(untitled) (Jurnal Destinasi Pariwisata, 2026)
This study aims to identify the potential and formulate appropriate strategies for the development of traditional culinary tourism in Blitar City Square. The research applies a descriptive qualitative method combined with SWOT analysis to obtain comprehensive findings. Data were collected through direct observation at the culinary center, in-depth interviews with traditional culinary business actors, officers of the Tourism Department, and tourists visiting the square, as well as documentation studies to strengthen the validity of the data. The results of the study indicate that Blitar’s traditional culinary delights such as Tahu Lontong, Opak Gambir, Es Pleret, and Es Drop possess strong potential to be promoted as distinctive tourist attractions. These culinary products are not only appreciated for their unique flavors but also for their historical value and the role they play in shaping Blitar’s cultural identity. The friendliness and hospitality of culinary business owners further enhance the experience for visitors, creating a warm atmosphere that encourages repeat visits. Additionally, the annual cultural and culinary event “Blitar Djadoel” has proven to be an effective promotional medium, as it introduces traditional food to a wider audience and strengthens the nostalgic branding of Blitar City. Nevertheless, several challenges remain. Weaknesses identified include limited use of digital platforms for marketing, lack of continuous innovation in menu presentation, and environmental cleanliness issues around the culinary area. These factors may reduce the attractiveness of Blitar Square as a sustainable culinary tourism destination if not addressed properly. Based on the SWOT analysis, the SO (Strength–Opportunity) strategy is prioritized, which emphasizes maximizing internal strengths to capture external opportunities. Recommended actions include intensifying both offline and online promotional efforts, encouraging product innovation while preserving authenticity, and developing creative tourist experiences. Such steps are expected to increase tourist visits and strengthen Blitar City’s image as a culinary tourism destination with unique traditional characteristics.